Recovery of Gold Nanoparticles from Aqueous Solutions via Hydrogen Peroxide Reduction using Self-Propelled Palm Shell-Supported Manganese Dioxide Composites - Muhammad Irsyad Roslan; Nor Hasanah Zubaidi; Chan Juinn Chieh Derek; Eric D. van Hullebusch; Siu Hua Chang (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
Intensive mechanical stirring, commonly used for gold nanoparticle (AuNP) recovery, suffers from drawbacks such as mechanical wear and high operational costs. Self-propelled catalytic composites capable of autonomous motion present a promising alternative, yet their applicability and influence on AuNP recovery efficiency remain insufficiently explored. Hence, this study aimed to fabricate palm shell-supported manganese dioxide (MnO2)composites and investigate the effect of their dosage on AuNP recovery via hydrogen peroxide reduction. The composites were characterized using Field Emission Scanning Electron Microscopy with Energy Dispersive X-Ray Spectroscopy (FESEM-EDX) to assess their morphology, particle size, and elemental composition, while UV-Vis spectroscopy was used to monitor AuNP formation through localized surface plasmon resonance (LSPR) responses. Results revealed that a composite dosage of 0.2 g/L produced the sharpest LSPR peak at 530 nm, indicating the highest yield of spherical AuNPs with particle sizes ranging from 20 to 80 nm. Motion analysis showed that the composites exhibited autonomous bubble-propelled motion at an average speed of 25.5 µm/s, following linear and semi-circular trajectories that enhanced mass transfer and AuNP recovery efficiency. Overall, palm shell-supported MnO2 composites demonstrate great potential as an alternative to conventional mechanical stirring-based methods for recovering AuNPs. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).